Multicultural children’s books at the French Canadian public library: Where can I find them? - Dionne, Anne-Marie (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
This article presents the results of a content analysis of 1,132 picture books published by French Canadian editors from 2003 to 2012. We took into account the representations of members of visible minorities, as well as the cultural origins of the authors and illustrators. Results show important gaps between the Canadian demographic reality and the representation of visible minorities in picture books. Consequences of the scarcity of multicultural picture books on children’s development are discussed. A few strategies that public libraries can use to alleviate the situation are presented.